Adult gonococcal conjunctivitis: Prevalence, clinical features and complications. Issue 9 (8th September 2021) - Cuesta Chasco, Genoveva; Carreras-Castañer, Xavier; Zboromyrska, Yuliya; Pitart, Cristina; Palma-Carvajal, Francisco; Bosch, Jordi; Figueroa-Vercellino, Juan Pablo
Abstract : Introduction. Gonorrhoea is a sexually transmitted disease whose incidence has increased in recent years and adult gonococcal conjunctivitis (AGC) is a relatively uncommon complication. Hypothesis/Gap Statement. AGC is associated with increased incidence of genital gonorrhoea and must be treated correctly to avoid serious corneal complications. Aims. To report the prevalence, clinical features, and complications of AGC in a tertiary ophthalmology centre in Barcelona, Spain. Present epidemiological data, clinical features, ocular complications, and antibiotic susceptibility. Design: Single-centre, descriptive, retrospective case series. Methodology. Systematic case-defined search in medical records and further retrospective chart review study of microbiologically confirmed AGC attending outpatient clinic and/or emergency room from 2012 to 2020. We analysed the clinical presentation, treatments, antibiotic susceptibility, complications and ocular sequelae. Results. Thirteen patients were diagnosed of AGC. Eleven patients had unilateral presentation. Two patients had bilateral presentation. In ten cases there was abundant mucopurulent discharge, three cases presented periocular pain and periocular inflammation requiring a CT scan to rule out post-septal cellulitis. The diagnosis was confirmed by culture. In total, 100 % of strains were susceptible to ceftriaxone, 58 % were ciprofloxacin resistant and no beta-lactamase production was detected. Three patients required hospital admission. One patient developed a complication presenting with ptosis caused by superior symblepharon. Conclusion. AGC is a rare disease which is difficult to diagnose as it requires a high index of suspicion to prevent corneal perforation but in an important number of cases it may mimic orbital cellulitis. It is crucial that treatment starts as soon as possible to avoid serious corneal damage. Patients should promptly receive complete and correct treatment when admitted to the emergency room since an elevated number of patients do not attend their medical follow-up visit. Azithromycin or aminoglycoside eye drops are probably the best option to complete the treatment, due to high quinolone resistance.